1966
DOI: 10.1079/wps19660016
|View full text |Cite
|
Sign up to set email alerts
|

Cottonseed Meal for Poultry: from Research to Practical Application

Abstract: This review is dedicated to M i . Burt W. Heywang, Superintendent of the Southwest Poultry Experiment Station, Glendale. Arizona. For almost three decades Burt and his associates have enriched the scienific world with a vast amount of data relating to utilization of cottonseed products. This unobtrusive man is admired by all who have known him for his devotion to scientific integrity and thoroughness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
1
2

Year Published

1973
1973
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(33 citation statements)
references
References 138 publications
(182 reference statements)
0
30
1
2
Order By: Relevance
“…FG may result in yolk discoloration based on a chemical combination of gossypol with ferric iron (Fe +3 ) released from yolk proteins (Kemmerer et al, 1966). This effect is more pronounced in stored eggs (Phelps, 1966). In this study, yolk discoloration was not observed even in the highest FG concentration (28.35 mg/kg) in the LCSM 100 and FG groups.…”
Section: Discussionmentioning
confidence: 63%
“…FG may result in yolk discoloration based on a chemical combination of gossypol with ferric iron (Fe +3 ) released from yolk proteins (Kemmerer et al, 1966). This effect is more pronounced in stored eggs (Phelps, 1966). In this study, yolk discoloration was not observed even in the highest FG concentration (28.35 mg/kg) in the LCSM 100 and FG groups.…”
Section: Discussionmentioning
confidence: 63%
“…These two types of meals comprise about 70% of the U.S. cottonseed supply and usually contain 100-700 p.p.m. free gossypol (Phelps, 1966). The analysis of these meals are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Recent research, reviewed by Phelps (1966) has demonstrated that at least a portion of the poor results associated with feeding cottonseed meal could be attributed to a lysine deficiency or to the presence of cyclopropenoid fatty acids. Recognition of these factors, coupled with improved processing techniques, has made possible the utilization of a greater percentage of cottonseed meal in layer diets.…”
mentioning
confidence: 98%
“…The effects of dietary free gossypol on egg yolk discoloration and on laying hen performance have been reviewed by Phelps (1966) and by Waldroup (1981). The two factors that limit CSM use in laying hen diets are free gossypol level and the presence of cyclopropenoid fatty acids (CPFA) in the residual oil (Phelps et al, 1965).…”
Section: Introductionmentioning
confidence: 99%